2011
DOI: 10.1111/j.1574-6968.2010.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of butyryl CoA:acetate CoA-transferase genes reveals different butyrate production capacity in individuals according to diet and age

Abstract: The gastrointestinal microbiota produces short-chain fatty acids, especially butyrate, which affect colonic health, immune function and epigenetic regulation. To assess the effects of nutrition and aging on the production of butyrate, the butyryl-CoA:acetate CoA-transferase gene and population shifts of Clostridium clusters lV and XlVa, the main butyrate producers, were analysed. Faecal samples of young healthy omnivores (24 ± 2.5 years), vegetarians (26 ± 5 years) and elderly (86 ± 8 years) omnivores were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 28 publications
2
42
1
2
Order By: Relevance
“…Butyryl-CoA:acetate-CoA transferase is a key enzyme in the major pathway for bacterial butyrate production in the gut (7). Hippe et al showed that this enzyme is a suitable marker for the butyrate-producing capacity of the intestinal microbiota which mainly belong to Clostridium cluster IV and XIVa (51,52). We observed a significant increase of members from both clusters in the ceca of chickens that were administered XOS.…”
Section: Discussionsupporting
confidence: 58%
“…Butyryl-CoA:acetate-CoA transferase is a key enzyme in the major pathway for bacterial butyrate production in the gut (7). Hippe et al showed that this enzyme is a suitable marker for the butyrate-producing capacity of the intestinal microbiota which mainly belong to Clostridium cluster IV and XIVa (51,52). We observed a significant increase of members from both clusters in the ceca of chickens that were administered XOS.…”
Section: Discussionsupporting
confidence: 58%
“…The butyrate kinase pathway is more related to a Western diet, reflected in HFD fed mice (main fat resource: lard). Meanwhile the butyryl CoA: acetate CoA-transferase gene is associated with vegetarian feeding and to a lesser content available in omnivores [69]. …”
Section: Discussionmentioning
confidence: 99%
“…The overall abundance of butyrate-producing bacteria was determined by quantifying the amount of the butyryl CoA:acetate CoA-transferase (BCoAT) gene using the primers BCoATscrF/BCoATscrR (Supplementary Table 4) as described elsewhere5758. The BCoAT gene was amplified from 50 ng of metagenomic DNA in a 25 μl qPCR reaction containing 1 × QuantiTect SYBR Green PCR master mix (Qiagen) and 2.5 μM of BCoATscrF/BCoATscrR primers.…”
Section: Methodsmentioning
confidence: 99%